Folliculitis barbae caused by Staphylococcus lentus: a rarity with its dermoscopy features - Ankad, Balachandra S.; Smitha, Sankappanavar V.; Nikam, Balkrishna P.; Janagond, Anand B. (International Journal of Research in Dermatology, 2023)
Dermoscopy of folliculitis is typified by white roundish globules around the hair follicles. Clinically, folliculitis mimics pseudo folliculitis which results from close shaving of beard hairs. Thus, management in both is entirely different. Dermoscopy of latter entity reveals buried hair at both ends. Here, authors described a case of folliculitis caused by Staphylococcus lentus.